2021
DOI: 10.7554/elife.72051
|View full text |Cite
|
Sign up to set email alerts
|

S-acylation by ZDHHC20 targets ORAI1 channels to lipid rafts for efficient Ca2+ signaling by Jurkat T cell receptors at the immune synapse

Abstract: Efficient immune responses require Ca2+ fluxes across ORAI1 channels during engagement of T cell receptors (TCR) at the immune synapse (IS) between T cells and antigen presenting cells. Here, we show that ZDHHC20-mediated S-acylation of the ORAI1 channel at residue Cys143 promotes TCR recruitment and signaling at the IS. Cys143 mutations reduced ORAI1 currents and store-operated Ca2+ entry in HEK-293 cells and nearly abrogated long-lasting Ca2+ elevations, NFATC1 translocation, and IL-2 secretion evoked by TCR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
(61 reference statements)
6
23
0
Order By: Relevance
“…3B; (11)). It has been shown that DHHC20 S-acylates Orai1 (12). We have shown that many TCR pathway components are S-acylated by the PM-localized DHHC21 (25-28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B; (11)). It has been shown that DHHC20 S-acylates Orai1 (12). We have shown that many TCR pathway components are S-acylated by the PM-localized DHHC21 (25-28).…”
Section: Discussionmentioning
confidence: 99%
“…Another important observation from S-acylation of STIM1 and Orai1 is the importance of immunological synapse formation in the TCR-mediated immune response (29-31). S-acylation of Orai1 is important for segregation of the channel to the immunological synapse (12). In our previous studies, we have shown that several TCR components are rapidly and transiently S-acylated during T cell activation to regulate immune responses (25-27,32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is increasing evidence that cholesterolrich regions define the association and function of the STIM1/Orai1 complex [116,117]. On the one hand, the function of both STIM1 and Orai1 is modulated by direct interaction with lipids, including particularly cholesterol and the phospholipid PIP 2 [118][119][120][121][122][123]. On the other hand, there is plethora of evidence that the STIM1/Orai1 interplay is indirectly controlled via the spatially separated phospholipid bilayers, the ER and the PM, along with a variety of lipid-or ER-PM junction-dependent accessory proteins [124].…”
Section: Crac Channelsmentioning
confidence: 99%
“…The major lipids which regulate STIM1/Orai1 function via direct interaction are PIP 2 and cholesterol [25,[125][126][127]. Furthermore, there is evidence for sphingomyelin- [128] and S-acylation- [123] mediated modulation of CRAC channels (Figure 2). Phospholipids were hypothesized to contribute to LoF of certain STIM1 mutants [83].…”
Section: Lipids Directly Regulated Crac Channel Componentsmentioning
confidence: 99%
See 1 more Smart Citation